Recent advances in the development of anti-infective peptoids. Issue 76 (1st September 2020) - Bicker, Kevin L.; Cobb, Steven L
Abstract : This feature article highlights the progress that has been made towards the development of novel anti-infective peptoids and the key areas for future development within this field. Abstract : In the search for new sources of antimicrobials many researchers have investigated antimicrobial peptides (AMPs) as templates for the design of innovative therapeutics. However, efforts to develop AMPs in this area has been severely hampered by their inherent susceptibility to enzymatic degradation. Given this only a handful of AMPs are currently in clinical trials. Peptide mimetics such as peptoids have emerged as highly promising alternatives to AMPs as they are inherently stable to enzymatic degradation and display potent antimicrobial properties. This feature article highlights the progress that has been made towards the development of novel anti-infective peptoids.